STEM-Based E-Module Integrated with Virtual Scanning Electron Microscope (SEM): An Innovative Learning Material for Science Learning in Secondary School - Tyas, Intan Lestari Mulyaning; Sumiati, Ika Dewi (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2025)
This study aims to develop a STEM-based e-module integrated with a Virtual Scanning Electron Microscope (SEM) as an innovative solution in science learning. This study used the research and development method with the ADDIE model, which consists of five main stages: analysis, design, development, implementation, and evaluation. The study involved seventh-grade students in secondary school as the research subjects. The developed e-module was evaluated for validity in content, language, and presentation, and tested for practicality through readability responses and effectiveness using a quasi-experimental design. The results indicated that the developed e-module had high validity, practicality, and effectiveness. Expert validation rated the e-module as feasible, with the material component scoring 82.67, the language aspect rated at 88, and the presentation dimension reaching 87.3. The readability test demonstrated its practicality, showing that the e-module is user-friendly, engaging, and interactive, with the majority rating it as "very practical". Furthermore, its implementation in learning was proven to enhance students' achievement, as reflected by N-Gain scores ranging from medium to high, along with a large effect size, with an average value of 0.75 in the "high" category. Therefore, this developed e-module can be considered a relevant instructional innovation to support 21st-century science learning.